Allergy and pollinosis (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Allergic diseases are considered to be one of the most important contemporary health problems. The prevalence of these diseases is increasing regardless the age groups or environmental conditions all over the world. Therefore there is a strong need for a better understanding of mechanisms underlying allergic respiratory or skin pathology. Unfortunately there are still some questions to be answered before our knowledge will be satisfactory and our treatment will be effective in all clinical cases. This short paper presents some basic information on allergic inflammation in the case of respiratory and skin allergic diseases. It should be stressed that a close cooperation between clinical practitioners and aerobiologists in terms of pollination monitoring is absolutely crucial for a good prophylactic approach in allergology.